People conversing in a lobby - Unknown:::Creator::::::::::::
Negative shows two women in the middle of a conversation. They are holding cups and plates and are in a large lobby-like room with upholstered chairs, tables, and large potted plants. There is a crowd of men and women milling around in the background.